Currency Substitution in Latin America : Lessons from the 1990s - Gomis-Porqueras, Pere; Serrano, Carlos; Somuano, Alejandro (World Bank, Washington, DC, 2014)
The authors study how agents in Latin America allocate their balances between dollar-denominated and domestic currency-denominated accounts. They empirically determine the causes of currency substitution, its significance in recent banking crises, and the link between currency substitution, and volatility in macroeconomic aggregates. Their findings: The ratio of dollar deposits to broad money is strongly influenced by expectations of depreciation. They show that depositors in Latin America face some uncertainty and frictions when making their portfolio decisions. They explore the macroeconomic consequences of a dollarized economy. In particular, they find that, in the presence of currency substitution, past banking crises are good predictors of future crises. In other words, having a highly dollarized economy, increases the response of the banking system when there is a bad shock, which halts the outflow of capital. Once an economy is in crisis, however, having more dollar-denominated deposits in the banking system, increases the probability of a longer crisis in the future, because it increases exchange rate exposure in an already weak banking system. Finally, they show that the volatility of macroeconomic variables linked to the financial system, increases whenever the economy becomes more dollarized, which in turn makes the choice of monetary targets more difficult.